2022
DOI: 10.1111/pde.14925
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis: An update

Abstract: Tinea capitis is an important superficial infection and affects children globally. A literature review was conducted to identify recent findings and the current understanding of this fungal infection. Here, we highlight updates on important aspects of tinea capitis including advances in dermatophyte detection and diagnosis and comparing these new methods to more traditional techniques. Additionally, aspects of treating tinea capitis are discussed, including the importance of mycological confirmation and curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…We identi ed a point prevalence of 11% for tinea capitis, which is the most infectious and most common paediatric dermatophyte infection globally especially in low-income and resource-poor settings. 49,50 This compares with up to 20% of the general population in developing countries and more than 30% of children in some urban areas of the United States. 51 T. tonsurans was the only species cultured from hair pluck specimens in our cohort.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…We identi ed a point prevalence of 11% for tinea capitis, which is the most infectious and most common paediatric dermatophyte infection globally especially in low-income and resource-poor settings. 49,50 This compares with up to 20% of the general population in developing countries and more than 30% of children in some urban areas of the United States. 51 T. tonsurans was the only species cultured from hair pluck specimens in our cohort.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Terbinafine demonstrated superiority in treating T tonsurans and a similar efficacy in treating T violaceum, while griseofulvin was superior in treating M canis and other Microsporum species. 8,9 The off-label use of fluconazole and itraconazole to treat TC is gaining popularity, with limited trials showing increased evidence of their effectiveness. There is not much clinical evidence to support the use of other oral antifungals, including the newer azoles such as voriconazole or posaconazole.…”
Section: Treatmentmentioning
confidence: 99%
“…There is not much clinical evidence to support the use of other oral antifungals, including the newer azoles such as voriconazole or posaconazole. 9 Newer limited evidence has shown the off-label use of photodynamic therapy to be a promising alternative to systemic antifungal therapy in treating TC, pending validation by larger sample trials. 10 In my practice, I have found that severe cases of TC demonstrating inflammation or possible widespread id reactions are better treated with oral steroids.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations